2017
DOI: 10.18006/2017.5(1).014.021
|View full text |Cite
|
Sign up to set email alerts
|

Relatıonshıps between stomatal conductance and yıeld under defıcıt ırrıgatıon ın maıze (Zea mays L.)

Abstract: This study was conducted to evaluate the adaptability of maize hybrids under water deficit condition by measuring of stomatal conductance with the corresponding yield of maize hybrids. Seven maize hybrids were grown at two different irrigation regimes (well water and deficit water conditions) at the agricultural research area of Cukurova University, Adana, Turkey. The results of study indicated that at drought stress (deficit water) remarkably influenced maize yield. The hybrid Sancia produced maximum grain yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The reduction rate in grain yield under drought stress was 23 and 20 % in both seasons, respectively. Similar reduction in crops yield and yield related attributes under water deficit conditions was reported by Hassan et al (2016), EL Sabagh et al (2015), Rashwan et al (2016), EL Sabagh et al (2017) in different crops. Talebi et al (2010) reported that, under water stress conditions, biomass and plant height had more positive effect on grain yield, for this reason, the yield of grain reduced significantly under water stress mainly as a results of reduction in biomass, number of seed/spike and plant height .L7 and L11 genotypes that, produced high values for MP, YSI, STI, GMP and YI and SSI less than one, and low values of TOL.…”
Section: Sti-stress Tolerance Index Yi-yield Index Ysi-yield Stabilsupporting
confidence: 85%
“…The reduction rate in grain yield under drought stress was 23 and 20 % in both seasons, respectively. Similar reduction in crops yield and yield related attributes under water deficit conditions was reported by Hassan et al (2016), EL Sabagh et al (2015), Rashwan et al (2016), EL Sabagh et al (2017) in different crops. Talebi et al (2010) reported that, under water stress conditions, biomass and plant height had more positive effect on grain yield, for this reason, the yield of grain reduced significantly under water stress mainly as a results of reduction in biomass, number of seed/spike and plant height .L7 and L11 genotypes that, produced high values for MP, YSI, STI, GMP and YI and SSI less than one, and low values of TOL.…”
Section: Sti-stress Tolerance Index Yi-yield Index Ysi-yield Stabilsupporting
confidence: 85%
“…The SL was invariably higher in number than SU but, overall their number was reduced due to WDS on both surfaces of the leaves viz; SL by 10.58% in NDT and 8.00% in DT); SU by 11.95% in NDT and 10.09% in DT. The stomatal conductance decreased, which has a direct proportional relationship with yield 36 . In maize, the flag leaf and the 2 nd leaf from the top are much smaller than the 3 rd leaf from the top (LA-3).…”
Section: Discussionmentioning
confidence: 95%
“…Water stress significantly decreased the transpiration rate (37%) and stomatal conductance (26%) of maize [99]. Nevertheless, the extent of decrease in stomatal conductance depends on the growing period when the water deficiency occurred; at 7 days after anthesis of maize cultivars stomatal conductance decreased by 35% on average but at 21 days after anthesis this decrease was significantly larger (74%) under water deficiency than in well-watered cultivars [100]. In the case of tomatoes grown under non-irrigated conditions, stomatal conductance decreases from 14 to 73% depending on the weather and variety in comparison with the well-watered plants [3,32,87,101] (Table 3).…”
Section: Stomatal Conductancementioning
confidence: 97%